Passion, paternalism, and politics: DIY development and independent volunteers in Honduras. Issue 6 (18th August 2017) - McLennan, Sharon J.
ABSTRACT: Independent development volunteers (IDVs) and their DIY development projects, although largely neglected in the literature, are part of an emerging movement of non-traditional agents within development. However, they are also participants in a deeply paradoxical industry; both a reflection of passion and commitment, and a paternalist and neo-colonial practice that reflects the messy realities of geo-political and cultural power and privilege. This article explores these debates, drawing on research with IDVs in Honduras. The intersection of passion, paternalism, and politics highlights the complex environments in which IDVs work, and the need to make them visible in discussions of development.